Salaam Bombay! - Nair, Mira.; Taraporevala, Sooni, 1957-; Syed, Shafiq; Vithal, Hansa; Sharma, Chanda; Kanwar, Aneeta; Yadav, Raghuvir; Patekar, Nana, 1951-; N.F.D.C. Doordarshan (Firm); Mirabai Films (Firm) (New Delhi, India : Eagle Home Video, 2005)
Krisha, a ten year old boy, has been abandoned in Bombay by his mother. While living in the streets, he tries to earn money to go home.
Videodisc release of the 1988 motion picture.
Editor, Barry Alexander Brown; music, L. Subramaniam ; director of photography, Sandi Sissel.
Shafiq Syed, Hansa Vithal, Chandra Sharma, Aneeta Kanwar, Raghubir Yadav, Nana Patekar.
DVD, all regions, Dolby Digital 5.1.
Soundtrack in Hindi with English subtitles.
Keywords: Homeless youth -- India -- Mumbai -- Fiction; Homeless youth -- India -- Mumbai -- Drama; Mumbai (India) -- Social conditions -- Fiction; Mumbai (India) -- Social conditions -- Drama; Feature films; Feature films; Youth -- Feature